Maieusis essays on ancient philosophy in honour of Myles Burnyeat - Burnyeat, Myles; Scott, Dominic (Oxford : Oxford University Press, 2007)
'Maieusis' pays tribute to the highly influential work of Myles Burnyeat, whose contributions to the study of ancient philosophy have done much to enhance the profile of the subject around the world.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Philosophy, Ancient